2021
DOI: 10.3389/fimmu.2021.699128
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Dendritic Cells Induced by Bendamustine Are Associated With Enhanced Flt3 Expression and Alloreactive T-Cell Death

Abstract: The growth factor Flt3 ligand (Flt3L) is central to dendritic cell (DC) homeostasis and development, controlling survival and expansion by binding to Flt3 receptor tyrosine kinase on the surface of DCs. In the context of hematopoietic cell transplantation, Flt3L has been found to suppress graft-versus-host disease (GvHD), specifically via host DCs. We previously reported that the pre-transplant conditioning regimen consisting of bendamustine (BEN) and total body irradiation (TBI) results in significantly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…A body of literature has only recently started to emerge, in large part from our group ( 2 , 10 14 ), regarding the immunomodulatory properties of BEN on MDSCs, DC subsets, and T cells ( 10 14 ). In all our murine models, whether BEN is given pre- or post-transplant, it has been associated with decreased GvHD and increased GvL.…”
mentioning
confidence: 99%
“…A body of literature has only recently started to emerge, in large part from our group ( 2 , 10 14 ), regarding the immunomodulatory properties of BEN on MDSCs, DC subsets, and T cells ( 10 14 ). In all our murine models, whether BEN is given pre- or post-transplant, it has been associated with decreased GvHD and increased GvL.…”
mentioning
confidence: 99%
“…However, as viral reactivation due to delayed immune reconstitution and relapse often lead to morbidity and mortality of patients ( 3 , 6 , 28 30 ), some investigators have begun evaluating a reduction in the dose of post-transplant CY to limit these complications ( 8 , 10 , 11 ). Our laboratory has taken a different approach in evaluating whether partially replacing PT-CY with post-transplant bendamustine (PT-BEN) would be advantageous, which is based on our extensive research that has delineated several immunomodulatory properties of BEN on myeloid derived suppressive cells (MDSCs) and dendritic cell (DC) subsets ( 14 16 ). Moreover, we have demonstrated that BEN yields tolerant T-cells with a striking absence of GvHD, while preserving T-cell dependent graft-versus-tumor (GvT) effects ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that using BEN as either a component of a pre-transplant conditioning regimen or when used in a post-transplant setting led to equal or improved survival in mice undergoing major histocompatibility complex (MHC) mismatched or haploidentical bone marrow transplants (haplo-BMT), respectively ( 12 , 13 ). BEN was shown to modulate immune cell number and function in transplanted mice, with increases in regulatory-like dendritic cells (DCs) ( 14 , 15 ) and myeloid-derived suppressor cells (MDSCs) ( 16 ), reduced proliferation of B and T cells, and a higher presence of T cells that are tolerized towards host MHC molecules ( 12 ). Importantly, BEN treated animals, in both pre-transplant and post-transplant settings, had superior GvT effects with reduced tumor burden and improved survival compared to those treated with CY ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The same group exposed murine bone marrow-derived dendritic cells (BMDC) to bendamustine and incubated them with allogenic T-cells. Upon incubation, T-cells exhibited an increase in markers of T-cell exhaustion, as well as markers of activated T-cells, ICOS and CD69, and an increase in PD-1, negative regulator of immune response, followed by allogenic CD4 + cell death (96). Since PD-1 is so far considered to be crucial in T-cell exhaustion, combining bendamustine with anti-PD-1 antibody could be beneficial in both anticancer and anti-microbe setting (97).…”
Section: Immunological Effects Of Bendamustinementioning
confidence: 99%